PEMBERDAYAAN MASYARAKAT MENGELOLA LIMBAH PLASTIK MENJADI ECOBRIK DI DESA TANJUNG GUNUNG - Rosmawati, Rosmawati; Ega, Henny Egawati; Arsuni, Arsuni (AbdiMuh : Jurnal Pengabdian Masyarakat, 2024)
The volume of waste from year to year is increasing, so a solution is needed so that waste waste does not accumulate, one of which is by making ecobric works, where the manufacture requires quite a lot of plastic waste so that it can be said that ecobric is one of the innovations that can be utilized in reducing plastic waste waste. In this service activity, it is focused on processing waste back to housewives in Tanjung Gunung village. With the aim that the community can know that from garbage that usually goes directly into the trash box, it can become useful items in everyday life, and so that ecobric can be applied in life, so that the environment can be kept clean. The method used is counseling and socialization to housewives in the village of Tanjung Gunung, that plastic waste can still be reprocessed into various useful products in everyday life. Socialization and naming activities were carried out with housewives of Tnjung Gunung village, the activity was enthusiastically welcomed by the housewives, then the mothers heard an explanation of the steps in making ecobric. Group members also participated in making the work so that the activity ran smoothly.Abstract is written in English and Indonesian (except articles written in English) which contain key issues, research objectives, methods / approaches and research results. Abstract is written in one paragraph, no more than 200 words. (Times New Roman 11, single space, and italics), a maximum of 1 page.